What Is Behind the Window? Ontological Question of Spiritual Experience Between Rudolf Otto and Carl Gustav Jung - Andrej Rajský (Society for Spirituality Studies, 2021)
The fundamental question of the presented study is the question of ontological status of experience with the Sacred: Where does spiritual experience belong – to the world of facts or to metaphysics? Or somewhere in between? The world of empirical experiencing is mediated to us by the science of psychology, which looks at the experience with the Sacred “from the inside”, focusing on what is happening “in front of the window”, that is, in our consciousness. The world of metaphysics offers speculative answers to what “is” reality that is situated “behind the window”, that is, in the sphere of being to which we do not have a direct evidential approach. Is it possible to say “something” about the Numinous in such a way so that it is not a mere projection of our own images? This question is answered in the study with the aid of the approach of philosophical phenomenology of religion offered by Rudolf Otto and it is applied here to depth-psychological conceptions of spirituality. According to Rudolf Otto, the divine “insisting presence” (Lat. numen) bears on man’s psyche and calls them to various demonstrations of cult or spontaneous devotion, i.e., reverence to transcendence. The initial depth psychology led by Freudian psychoanalysis describes religious notions as illusory projections of unconsciousness or “neurosis of humanity”. However, skepticism of the Enlightenment era, the self-sufficient science of which was supposed to lead us, proved to be another form of dogmatism and its arrogance was fully exposed at the end of the 20th century. When asked whether the experience of the Numinous is only a symbol of collective ideas (C. G. Jung) or the result of a dialogue between a subject and a certain essential ontological pendant of religious experience (V. White), the author inclines to the second, meta-ontic attitude, which he clarifies in the study.